Controlling COVID-19 spread in Jakarta, Indonesia, using quarantine, testing and medical treatment - Fitri, Ihza Rizkia; Bakhtiar, Toni (Kuwait Journal of Science, 2021)
The SARS-CoV-2 outbreak that started in China creates COVID-19 pandemic all around the world. This pandemic is declared as a world health crisis by the World Health Organization in 2020. As responses to this pandemic, many countries have been conducting various measures to manage the spread of the disease by means of lockdown, contacts tracing, and massive testing. As the vaccine and medicine for this virus are under development, the governments all around the world can only apply non-curative measures. With many considerations, especially in the economic sector, governments seem hesitant to apply extensive control measures and this results in a considerable economic loss. In this paper, a generic mathematical model with thirteen compartments is developed, of which it is equipped with five control measures namely quarantine, active carrier identification, recovered individual identification, past infection identification, and medical treatment. We employ the COVID-19 outbreak in Jakarta as a study case to evaluate a series of control scenarios. Optimal control approach is used to find the best control strategy in managing the pandemic. It is suggested that adding the efforts on testing policy and medical treatment 40 days after the first confirmed infection is the most cost-effective strategy with the number of death decreased as much as 60.21 percent of the death cases under initial control strategy.